Practices of Coexistence : Constructions of the Other in Early Modern Perceptions - Birnbaum, Marianna D.; Sebők, Marcell (Book collections on Project MUSE., 2017)
The essays in this book provide interesting contributions to the ongoing debate concerning the "image of the Other" in the early modern period. They deal with images, representations, projections, and perceptions, based on various experiences of coexistence. Although the individual contributions contain sources and references of iconography, this is not just another volume of art history or visual studies. As examples of practices in diverse historical contexts, the book includes a variety of textual material, such as literary productions, rhetorical exercises, dramatic applications, chronicle.